The Concept of Justice in The Qur’an and Hadith (Study of Quraish Shihab’s Interpretation QS. An-Nisa: 135 on Youtube) - Laily Liddini; Ade Surya Wilia Prabandani; Wardatun Nadhiroh (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
The emergence of Youtube is a sign of the presence of new media in interpreting the Qur'an. This article aims to analyze the interpretation of the Qur'an by M. Quraish Shihab, who uses YouTube as his medium, which was conveyed in the Ramadan talk show “Tafsir al-Misbah” on Metro TV, especially the episode of the interpretation of the Quran Surah al-Nisâ' verse 153. The purpose of the research seeks to find out the meaning of justice in QS. An-Nisa verse 135, and also an analysis of Quraish Shihab's interpretation of the command to uphold justice and testify in the verse. While this article is written using qualitative methods with analytical descriptive analysis. The results of this study indicate that the interpretation conveyed by M Quraish Shihab through Youtube has characteristics that focus on linguistic approaches presented in a thematic form, with the nuances of adab-ijtima'i, bi ra'yi, and discussion in generally and globally. This is what the writing contributes to fill in the gaps where the discussion of interpretation is usually concerned with the book of interpretation. According to him, justice is an order to uphold justice and be fair in witnessing with near perfection.